2019
DOI: 10.1111/febs.14993
|View full text |Cite
|
Sign up to set email alerts
|

A biophysical and structural study of two chitinases from Agave tequilana and their potential role as defense proteins

Abstract: Plant chitinases are enzymes that have several functions, including providing protection against pathogens. Agave tequilana is an economically important plant that is poorly studied. Here, we identified a chitinase from short reads of the A. tequilana transcriptome (AtChi1). A second chitinase, differing by only six residues from the first, was isolated from total RNA of plants infected with Fusarium oxysporum (AtChi2). Both enzymes were overexpressed in Escherichia coli and analysis of their sequences indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
3
2
0
Order By: Relevance
“…The optimum pH and temperature ranges over which these chitinases were stable were in the range of those reported for other reported plant, fungi and bacterial chitinases ( Patel et al., 2009 ; Sukprasirt and Wititsuwannakul, 2014 ; Horiuchi et al., 2016 ; Thimoteo et al., 2017 ; Wang et al., 2019 ; Rajninec et al., 2020 , Supplementary Table S4 ). The pH optimum and pH range for Os Chi19A activity are consistent with those reported for other plant chitinases ( Patel et al., 2009 ; Sukprasirt and Wititsuwannakul, 2014 ; Horiuchi et al., 2016 ; Sierra-Gómez et al., 2019 ; Wang et al., 2019 ). However, unlike other reported plants and bacterial chitinases, all of which have reported pH optima between 4.5 and 6, Zm Chi19A and Csp Ch18A were most active at pH 8.…”
Section: Discussionsupporting
confidence: 86%
“…The optimum pH and temperature ranges over which these chitinases were stable were in the range of those reported for other reported plant, fungi and bacterial chitinases ( Patel et al., 2009 ; Sukprasirt and Wititsuwannakul, 2014 ; Horiuchi et al., 2016 ; Thimoteo et al., 2017 ; Wang et al., 2019 ; Rajninec et al., 2020 , Supplementary Table S4 ). The pH optimum and pH range for Os Chi19A activity are consistent with those reported for other plant chitinases ( Patel et al., 2009 ; Sukprasirt and Wititsuwannakul, 2014 ; Horiuchi et al., 2016 ; Sierra-Gómez et al., 2019 ; Wang et al., 2019 ). However, unlike other reported plants and bacterial chitinases, all of which have reported pH optima between 4.5 and 6, Zm Chi19A and Csp Ch18A were most active at pH 8.…”
Section: Discussionsupporting
confidence: 86%
“…This reiterated that the change in aa residues on the surface‐exposed loop III could be a potential reason for the difference in efficacies of chitinases in our study 6 . Additionally, it has been reported that aa changes in other regions (outside of CD) also could bring conformational changes in the catalytic cleft of chitinases 47 . We therefore speculate that aa variations in CpCHI4 positively affected the (GlcNAc) 6 ligand accommodation process, thereby facilitating effective substrate binding and superior efficacy against the herbivore.…”
Section: Resultssupporting
confidence: 56%
“…Chitinases, also known as PR-3, are a group of proteins that protect plants against fungal diseases by cleaving the bonds between chitin molecules that are found in the fungal cell wall [50,51]. In the present study, compared to the uninfected control, a remarkable rise in PR-3, with a relative expression level of 5.76-fold at 20 dpi was reported (Figure 3).…”
Section: The Expression Levels Of Pr-related Genessupporting
confidence: 60%